2023
DOI: 10.3389/frmbi.2023.1194705
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide feed supplementation reduces plasma insulin in geldings with Equine Metabolic Syndrome

Alexandra von Münchow,
Sarah Torp Yttergren,
Rasmus Riemer Jakobsen
et al.

Abstract: BackgroundThe prevalence of Equine Metabolic Syndrome and insulin dysregulation is increasing in the horse population. Insulin dysregulation is a risk factor for laminitis, which has significant welfare consequences for the horse. Current treatment strategies for Equine Metabolic Syndrome have variable effects on insulin sensitivity. Findings suggest that gut microbiota plays an important role in gastrointestinal barrier protection and metabolic diseases. Dietary supplementation with oligosaccharides has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Thus, additional supplementation with commercially available feed balancer seems to be good solution. It has been demonstrated that oligosaccharide supplementation ameliorates insulin dysregulation ( 32 ), whereas a low dose of a synergistic polyphenol and amino acid blend including leucine improves metabolic health in EMS/insulin dysregulated horses ( 15 ). Furthermore, supplementation with omega-3 fatty acids would help to reduce problems associated with insulin resistance ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, additional supplementation with commercially available feed balancer seems to be good solution. It has been demonstrated that oligosaccharide supplementation ameliorates insulin dysregulation ( 32 ), whereas a low dose of a synergistic polyphenol and amino acid blend including leucine improves metabolic health in EMS/insulin dysregulated horses ( 15 ). Furthermore, supplementation with omega-3 fatty acids would help to reduce problems associated with insulin resistance ( 33 ).…”
Section: Discussionmentioning
confidence: 99%